Pengaruh Waktu Tinggal terhadap Efisiensi Penurunan Parameter pH, BOD, COD dan TSS dan Amoniak pada Air Limbah Domestik Menggunakan Tanaman Melati Air (Limnocharis flava) - Fajriaty, Rana; Asra, Revis; Gusti, Diah Riski (Universitas Batanghari Jambi, 2025)
This study aims to analyze the effect of the residence time of water jasmine plants in the form of genjer (Limnocharis flava) on its effectiveness in reducing the parameters of acidity (pH), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solid (TSS) and ammonia in domestic wastewater. The method used is an experiment with a Completely Randomized Design (CRD) design. The initial parameters of domestic wastewater showed pH 8.7, BOD5 209 mg/l, COD 412.73 mg/l, TSS 105 mg/l, and ammonia 45.22 mg/l. The results showed that the decrease in pH ranged from 4.21% to 17.62%, the decrease in BOD5 between 46.19% to 88.27%, the decrease in COD between 23.39% to 79.23%, the decrease in TSS between 76.22% to 79.25%, and the decrease in ammonia between 33.50% to 79.28%. The use of genjer plants in artificial wetlands with different residence times proved effective in reducing all these parameters, with a residence time of 9 days showing the most optimal results in reducing all parameters.